2020
DOI: 10.1111/ctr.14006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multidisciplinary multimodal opioid minimization initiative in kidney transplant recipients

Abstract: Opioid use after kidney transplant has been shown to be a risk factor for chronic opioid use, which leads to an increased risk of mortality. The purpose of this study was to evaluate the early impact of a multimodal pain regimen and education quality improvement program on opioid use after kidney transplant 2 months after implementation. This was a retrospective, single‐center analysis of post‐operative opioid use, comparing the average daily Morphine milligram equivalents (MME) of the patients who received ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Although admittedly studies analyzing posttransplant COU have shown even stronger associations with clinical outcomes than pretransplant opioid use, we feel it is a more clinically and operationally achievable goal to identify at‐risk patients and attempt to implement interventions to prevent COU after transplant than it is to mitigate COU and prevent outcomes once it has become already established. Recently, a multidisciplinary multimodal approach to mitigate posttransplant opioid use has shown excellent early outcomes by significantly reducing daily inpatient opioid use (38.6 vs. 8 morphine milligram equivalents/day, p < 0.001) and decreasing opioid prescriptions at discharge from 96% to 5% ( p < 0.001), but further analysis with larger samples and longer term follow‐up on both opioid use and clinical outcomes are necessary 13 …”
Section: Discussionmentioning
confidence: 99%
“…Although admittedly studies analyzing posttransplant COU have shown even stronger associations with clinical outcomes than pretransplant opioid use, we feel it is a more clinically and operationally achievable goal to identify at‐risk patients and attempt to implement interventions to prevent COU after transplant than it is to mitigate COU and prevent outcomes once it has become already established. Recently, a multidisciplinary multimodal approach to mitigate posttransplant opioid use has shown excellent early outcomes by significantly reducing daily inpatient opioid use (38.6 vs. 8 morphine milligram equivalents/day, p < 0.001) and decreasing opioid prescriptions at discharge from 96% to 5% ( p < 0.001), but further analysis with larger samples and longer term follow‐up on both opioid use and clinical outcomes are necessary 13 …”
Section: Discussionmentioning
confidence: 99%
“…Epidural anesthesia can be administered in these patients; however, its use is limited due to the hemodynamic effects and changes in coagulation. Regional methods, such as a transversus abdominis plane block, can be added to multimodal analgesia [37]. Similar to patients with kidney dysfunction, nonsteroidal anti-inflammatory drugs (NSAIDs) are not recommended in transplant recipients in the multimodal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the historical cohort (n = 48), the mean inpatient opioid dose was reduced with the protocol (8.0 vs 38.6 morphine mg equivalent/day, P < .001), and fewer patients were discharged with an opioid prescription (5% vs 96%, P < .001). 32 Multimodal analgesic regimens for kidney transplants often include TAP or QL blocks. Kolacz et al studied the impact of TAP versus QL on the postoperative opioid.…”
Section: Pain Managementmentioning
confidence: 99%
“…Multimodal analgesia and patient education may reduce the need for inpatient opioid administration and opioid prescriptions on discharge, which may provide long-term benefit. 31,32…”
Section: Pain Managementmentioning
confidence: 99%